Prevalence of impacted canine among Yemen population in Sana’a city - Lutf Al-Motareb, Fuad; Al-Labani, Mohammed A; M Al-Zubair, Nabil; Dhaifullah, Esam (International Journal of Dental Research, 2017)
Objective: Impacted maxillary and mandibular canine is a frequently encountered clinical problem. The objective of the present study was to determine the prevalence of impacted canine in patients visiting an Orthodontic Clinic in Sana'a city, Yemen.Materials and methods: Patients were examined in order to detect the impacted canines by radiographs. This study comprises data from randomly selected 5287 patients. Panoramic radiographs of 5287 were selected irrespective of sex, caste, nutritional and socio-economic status Angulation and depth of impacted canine were also assessed.Results: Out of 5287 surveyed subjects, 188 patients (3.55%) were determined to have canine impactions of whom 123 female and 65 male (Chi‑square = 18.667, df = 1, P = 0.00001). Of those determined with canine impaction, 168 presents with impacted maxillary canines, 8 presents with the impacted mandibular canine and 12 present with impacted canine in both maxillary and mandibular arch. The difference was statistically significant (Chi‑square = 157.362, df = 1, P = 0.0000). 138 subjects present with unilateral impaction, while the rest of the sample (50 subjects) present with bilateral impaction. Mesioangular impaction was found in 137subjects (68.5 %) and only 3 subjects (1.5 %) demonstrated distoangular impaction.Conclusion: Based on the study results, the canine impaction was reported in (3.55%) of Yemeni population included in the survey. Most of the canine impaction occurs in maxillary arch being more prevalent in female and unilateral in mesioangular direction.